How Complex is DNS? - Kakarla, Siva Kesava Reddy; Beckett, Ryan; Millstein, Todd; Varghese, George (HotNets 2021, 2021)
Motivated by recent results that show that Internet protocols can be surprisingly complex and, in particular, that BGP is Turing complete, we ask the same question for the Domain Name System (DNS). DNS is at least as pervasive and essential as BGP in the global Internet infrastructure. Besides the scientific interest, the complexity of DNS can have implications for new applications (that can utilize the unsuspected power of DNS), and for verification (to understand basic complexity limits and suggest new verification algorithms). In this paper, we show that using the power of DNAME records, DNS can express regular languages and pushdown systems. The first result can be used to build a system for controlling domain access (of which parental control is a special case). The second result shows that verification of DNS zone files is likely to take time that is at least cubic in the number of records.